Foliar water uptake and phyllosphere microbe colonization increase under higher soil nitrogen availability - Palmeri, Marcela Ailén (2024)
Leaf water uptake (FWU) represents an alternative pathway to plant water acquisition that can have positive effects on water and carbon balance. Leaf surface traits including the phyllosphere microbes can affect the leaf wetness capacity and FWU. These functional and structural leaf traits could change depending on soil resources availability. The aim of this study was to evaluate the responses of FWU and leaf surface traits such as contact angle, water drop adhesion (LWA) and phyllosphere-associated microbiota to soil nitrogen addition. Three dominant plant species, Azorella prolifera, Senecio filaginoides, and Papostippa speciosa, of an arid steppe in Patagonia exposed to nitrogen (+N) and nitrogen plus water (+NW) addition for ten years were selected. Leaf contact angle did not exhibit statistical differences among treatments within species. LWA was higher in all treatments with respect to the control (C) for shrub A. prolifera and grass P. speciosa. Nitrogen addition increased significantly FWU in A. prolifera and in P. speciosa with respect to C. Colony-forming units of culturable microorganisms (CFU) on leaf surface responded to N addition, but the changes were statistically significant in S. filaginoides and P. speciosa in +NW, increasing three and eight times, respectively, in relation to the C. A positive linear relationship was found between FWU and LWA across species and treatments. On the other hand, CFU of phyllosphere was negative and exponentially correlated with LWA and FWU, across species and treatments. The results suggest that soil N enrichment could affect functional leaf traits and phyllosphere microbiota in a way that may confer a higher potential to cope with drought by facilitating the use of alternative water sources. On the other hand, we suggested that species with leaves more colonized have less surface exposed for FWU and could have lower wettability depending on the hydrophobicity degree of microbes. However, a higher cover of epiphyte’s microorganisms could compensate the effects of lower FWU by avoiding the leaf dehydration. This study contributes to a better understanding of plant leaf-microbe interactions under higher N atmospheric deposition and intensive fertilization as global agricultural production is expected to increase.